Basic Electronics:a text-lab manual - Zbar, Paul B.; Malvino, Albert P.; Miller, Michael A. (New Delhi : Tata McGrow Hill, 1994)
Engineering
Keywords: Electronics; Electronics Text; Audioelectronics; Electronic Circuits; Electronic Technology; Toubleshooting; Zener Regulator; Optoelectronic Devices; Diode Limiter; Power Supply; Bridge Rectifier; Transistor Familiarization; Transistor Testing; Differential Amplifier; Operational Amplifier; Voltage Regulation; Intergated Circuits